The Law and an Ancestral Request For Exhumation - Magda Slabbert (Obiter, 2021)
Exhumation is the removal of the remains of a dead body from its initial resting place – in other words, when a corpse is removed from a coffin, either to be re-buried at another place, or to dispose of the remains in a different manner as in cremation. A corpse could be the remains of a deceased person or a stillborn child or a fetus. An exhumation may also be undertaken to ascertain the cause of death or to ascertain the identity of the deceased. A court or the immediate family of the deceased may request an exhumation for any of the mentioned reasons. If the family is asked by the ancestors to exhume a grave, certain legal questions may come to the fore. It is the purpose of this note to discuss the legal requirements for exhumations and briefly to address the traditional African cultural belief in which ancestors play a part in life on earth. It is not a complete analysis or an opinion on African culture or beliefs. Ancestral beliefs simply form the background to the real legal questions surrounding exhumations in South Africa.